Penggunaan limbah ikan tuna dan limbah tahu dalam formulasi pakan bagi pertumbuhan, efisiensi pakan, dan kelangsungan hidup ikan Nila salin (Oreochromis niloticus) - Ursula Pinontoan; Henneke Pangkey; Ockstan J. Kalesaran; Edwin L.A. Ngangi; Lusia Manu; Jeffrie F. Mokolensang (Universitas Sam Ratulangi, 2023)
This study aims to determine the adequacy of feed because of fish waste and tofu leftover flour for the development of saline tilapia, feed efficiency, feed conversion ratio, and survival rate. This examination was directed at the Laboratorium Technology Aquaculture. The quantity of fish taken was 300 tilapia fish with a size of 5–6 cm and a typical load of 5 grams. The test feed to be utilized in this review was formed from different fundamental fixings utilized, then, at that point, added with fish waste and tofu squander. In light of the consequences of the examination of the impact of various feed equations, specifically fish waste and tofu leftovers, they significantly affect the growth of saline tilapia. Different feed recipes influence the development of saline tilapia. From the consequences of exploration on saline tilapia, freshwater fish can inhabit a saltiness of 20 ppt in a controlled holder in one month or less. Of all the development boundaries estimated in this review, feed 3 was the best contrasted with different feeds. The aftereffects of the investigation of the change showed that the feed detailing was unique to that of fish waste and tofu residue, and the impact was exceptionally huge. Keywords: tilapia, growing, feed efficiency, feed conversion, survival